Supporting a Physical Self-Access Center with a Virtual Presence - Troy Rubesch; Keith Barrs (Studies in Self-Access Learning Journal, 2014)
This article describes the motivation and reasoning behind an ongoing project to create an online presence of a Self-Access Center (SAC). The project involves the selection and integration of a number of technologies which work to together to supplement the physical SAC. The authors argue that such projects have value both for the institutions which host them, and also for the learners they serve, such as support of individualized and independent learning, promotion of the SAC, and hosting and archiving resources. Establishing an online presence allows learners much greater freedom in when, where, what, and how they study.